THE IMPLEMENTATION OF ADIWIYATA PROGRAM VIEWED FROM THE ASPECT OF PARTICIPATORY – BASED ACTIVITIES AT SDN SERAYU - Lisa Retnasari; Yayuk Hidayah, Cahyo Ari Witanto, Anis Suryaningsih (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
This research was initiated by environmental problems that resulted in the significance to conduct research on environmental protection and management. One of the efforts to protect and manage the environment was Adiwiyata program in order to build students’ caring character and environmental culture. The purpose of this study was to describe the Adiwiyata Program in terms of participatory-based activities at SD N Serayu Yogyakarta. The type of this research was a qualitative descriptive study with a qualitative approach through a survey. The research subjects were the principal, 2 Adiwiyata teams, 2 classroom teachers, and 5 students. The object of research was the Adiwiyata Program Implementation in terms of participatory activity aspects. Then, data were collected through observation, interview, and documentation. The validity of the data was examined by technical triangulation and source triangulation. After that, the data were analyzed by using the Miles and Hubermen model. The results showed that the implementation of Adiwiyata Program viewed from participatory-based activities at SD N Serayu was running well. This could be seen from 1) implementing planned environmental protection and management activities for school residents which were carried out regularly and involved all school members; 2) establishing partnerships in the context of environmental protection and management with various parties including the Environmental Service, the Environmental Agency, committees, parents, RT, RW, Dukuh, Lurah, and Camat.